A tunable filter for high molecular weight DNA selection and linked-read sequencing. Issue 1 (4th December 2019) - Milon, Nicolas; Fuentes Rojas, Juan-Luis; Castinel, Adrien; Bigot, Laurent; Bouwmans, Géraud; Baudelle, Karen; Boutonnet, Audrey; Gibert, Audrey; Bouchez, Olivier; Donnadieu, Cécile; Ginot, Frédéric; Bancaud, Aurélien
Abstract : In third generation sequencing, long DNA molecules of more than ∼20 kbp are needed to obtain quality sequence data. Here we report a versatile technology for DNA size selection that fulfills this requirement. Abstract : In third generation sequencing, the production of quality data requires the selection of molecules longer than ∼20 kbp, but the size selection threshold of most purification technologies is smaller than this target. Here, we describe a technology operated in a capillary with a tunable selection threshold in the range of 3 to 40 kbp controlled by an electric field. We demonstrate that the selection cut-off is sharp, the purification yield is high, and the purification throughput is scalable. We also provide an analytical model that the actuation settings of the filter. The selection of high molecular weight genomic DNA from the melon Cucumis melo L., a diploid organism of ∼0.45 Gbp, is then reported. Linked-read sequencing data show that the N50 phase block size, which scores the correct representation of two chromosomes, is enhanced by a factor of 2 after size selection, establishing the relevance and versatility of our technology.